INTEGRASI NILAI KEARIFAN LOKAL DALAM PENDIDIKAN KERUKUNAN UMAT BERAGAMA DI SEKOLAH DASAR/MADRASAH IBTIDAIYAH (SD/MI) KOTA JAYAPURA - Rofiki, A. Arif (JMIE (Journal of Madrasah Ibtidaiyah Education), 2018)
Local wisdom of the people of Jayapura City in the tradition of Satu Tungku Tiga Batu can be utilized in the education of religious harmony at elementary level of primary school. The synergy of religion and culture through local wisdom One Three Stone Furnace is effective to realize religious harmony in the midst of plurality of tribe, religion, and race in Jayapura City, so that there has never been found any conflict and violence with religion background in Jayapura City. This paper aims to examine the local wisdom of One Three Stone Stoves and its integration in the education of religious harmony. Two findings that can be described in this study are: First: Local Wisdom One Three Stone Furnace plays a role in fostering and maintaining harmony among religious people that are dynamic, humanist and democratic in Jayapura City. Second, the contextualization of religious harmony education with the real life of learners can be done with the integration of local wisdom values in the strengthening of thematic learning materials in SD/MI.               The education of religious harmony needs to be strengthened since childhood at the level of basic education. The role can be optimally applied one of them by integrating the value of local wisdom on learning materials of learners to be more contextual with their daily life. The recommendations of this paper are: (1) The government should give more attention in the effort to cultivate the values through education level. Government policy in preparing facilities and other needs is still expected to be sustainability. (2) The value of local wisdom in strengthening the thematic learning materials in SD/MI is important to be done by educators as the implementation of curriculum 2013. It is hoped that with such integration, learners are more aware of the importance of growing and maintaining the harmony of religious communities in their surroundings.